Impact of Vocational Core Competencies of Higher Vocational Students on Innovative Behavior: The Mediating Effect of Creative Self-Efficacy and Moderating Effect of Core Self-Evaluation - Xin Xie; You Yu; Weiyu Wang (SAGE Open, 2023)
The cultivation of vocational core competencies is one of the essential guarantees to realizing students’ overall development. It is also a key quality and ability to promote students’ adaptation to lifelong development and career requirements. In this study involving 844 higher vocational students in Beijing, we analyzed the effect of vocational core competencies on innovative behavior. We find that sophisticated relationships exist between vocational core competencies, creative self-efficacy, innovative behaviors, and core self-evaluation. Innovative behavior positively correlated with vocational core competencies, in which creative self-efficacy has a partial mediating effect, positively regulated by core self-evaluation. Thus, higher vocational colleges should emphasize developing vocational core competencies systems and cultivating students’ innovative behaviors to promote all-around development.